Relationship between Service Quality and Customer Repurchase Intention in Cafés of Kathmandu Valley, Nepal - Rasaily, Prajwal; Shah, Nitesh Kumar; Adhikari, Bibhav (Quest Journal of Management and Social Sciences, 2023)
Background: Customer Repurchase Intention (CRI) refers to a customer's willingness to purchase again from the same business in the future, influenced by service quality in cafes. However, there has been a lack of clear scientific research evidence to understand which service quality dimension leads to customer repurchase in café. Objectives: The study aimed to determine the relationship between service quality and customer repurchase intention in cafés. Methods: A descriptive research design was used, using cross-sectional data collected from 160 respondents. We used correlation analysis and descriptive statistics to analyze the data using SPSS. Results: The findings showed that 80% of the respondents have a high repurchase intention from cafes in Kathmandu. The study identified reliability as the most important dimension determining customer repurchase intention, followed by tangibles, assurance, responsiveness, and empathy ranked the lowest. All the dimensions affected customer repurchase intention except responsiveness, which was statistically insignificant to customer repurchase intention. Demographic factors such as age, marital status, employment status, annual income, and the number of years visited in cafes create differences in customer repurchase intention. Interestingly, academic qualifications did not make any difference. Conclusion: The respondents exhibited that they were likely to repurchase. Based on service quality, reliability ranked highest, tangibles ranked second, assurance ranked third, responsiveness ranked fourth, and empathy ranked least, due to which café businesses must focus more on high-ranking factors for better customer repurchase in the future. Paper Type: Research Paper JEL Classification: L83, L80, L26